MOTIVATION OF ACCOUNTING STUDENTS IN REMOTE TEACHING IN THE LIGHT OF THE THEORY OF SELF-DETERMINATION - Carvalho Lopes, Cristiano (2024)
This research aimed to evaluate the level of motivation of Accounting students in relation to the transition from face-to-face teaching to remote teaching in the light of the Self-Determination Theory. The sample of this research was formed by 182 students who maintained active enrollment in the second semester of 2021. The study is characterized as descriptive, explanatory and quantitative, operationalized through an online questionnaire sent to students through a survey. The results of the study were partially convergent with those found in previous studies, probably due to the pandemic context. It is understood that students are motivated by external and identified regulation, followed by intrinsic motivation: they want to achieve a successful life in the future and are motivated to learn and expand their knowledge. With regard to contributions, it is presumed that this study can stimulate researchers in the accounting area to identify the factors that influence the students' demotivation. And, with that, they seek alternatives, through pedagogical strategies that make it possible to create conditions for students to remain intrinsically motivated in the course.